Fetal Epicardial Fat Thickness: Its Role as Marker for Gestational Diabetic Mellitus - Singh, Amandeep; Josan, Amitojveer S.; Gupta, Kamlesh; Pahwa, Sangeeta (Indian Journal of Radiology and Imaging, 2023)
Background There are very few studies on the association between fetal epicardial fat thickness (EFT) and gestational diabetes mellitus (GDM).Aims To evaluate the role of fetal epicardial fat thickness as a marker and use it in pregnancies to screen for GDM.Settings and Design A cross-sectional analytical study was conducted in the Department of Radiodiagnosis and Imaging at Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar, after the due clearance from the institutional research and ethics committee.Materials and Methods The study included pregnant patients at 24 + 0/6 to 28 + 0/6 weeks of gestation scheduled for a 75 g oral glucose tolerance test from December 1, 2020 to March 30, 2022. Antenatal ultrasound was performed on Voluson E8 Expert BT12 (Wipro GE) ultrasound machine. Out of 180 patients, 60 patients were selected, that is, 30 patients with raised 75 g OGTT results (cases of GDM) and 30 patients with normal 75 g OGTT results.Statistical Analysis The collected data were transformed into variables, coded, and entered into Microsoft Excel. Data were analyzed using the Shapiro–Wilk normality test, student's t-test or Mann–Whiney U test, chi-square test, or Fisher's exact test and statistically evaluated using the SPSS-PC-25 version.Results Fetal EFT was found to be significantly more in the GDM group in comparison to controls without GDM, and the increased fetal EFT was positively associated with 2-hour OGTT serum glucose values.The mean fetal epicardial fat thickness (EFT) in mothers with GDM was significantly larger, i.e., 0.17 ± 0.02 cm than in mothers without GDM, i.e., 0.12 ± 0.01 cm (p < 0.001). The receiver operating characteristic (ROC) curve plotted from values calculated from our results shows high sensitivity (i.e., 96.67%) and specificity (i.e., 90%) of fetal EFT as a predictor for GDM with an AUROC value of 0.96 and 95% confidence interval of 0.92 to 1.0.Conclusions EFT was significantly higher in fetuses of diabetic versus nondiabetic mothers. The mean difference in EFT of GDM cases and controls was relatively small but was statistically significant. The study concluded that measuring the epicardial fat thickness in fetuses can serve as a novel marker in GDM.
Keywords: epicardial fat thickness; fetal; gestational diabetes